Identification and Characterization of the Amphioxus Lck and Its Associated Tyrosine Phosphorylation-Dependent Inhibitory LRR Receptor - Zhou, Jiatao; Xiao, Zhihui; Zhan, Yanli; Qu, Xuemei; Mou, Sisi; Deng, Chong; Zhang, Tianxiang; Lan, Xin; Huang, Shengfeng; Li, Yingqiu (Frontiers in Immunology, 2021)
Amphioxus (e.g., Branchiostoma belcheri, Bb) has recently emerged as a new model for studying the evolution of vertebrate immunity. Here, we identified and cloned the amphioxus homolog of human lymphocyte-specific tyrosine kinase (Lck), which binds to CD4 and CD8 coreceptors of the T-cell antigen receptor (TCR) and initiates TCR signaling by triggering a cascade of tyrosine phosphorylation and phosphorylates both the ITIM and ITSM of PD-1 to activate its inhibitory function. By generating and using an antibody against BbLck, we found that BbLck is expressed in the amphioxus gut and gill. Through overexpression of BbLck in Jurkat T cells, we found that upon TCR stimulation, BbLck was subjected to tyrosine phosphorylation and could partially rescue Lck-dependent tyrosine phosphorylation in Lck-knockdown T cells. Mass spectrometric analysis of BbLck immunoprecipitates from amphioxus, revealed a BbLck-associated membrane-bound receptor LRR (BbLcLRR). By overexpressing BbLcLRR in Jurkat T cells, we demonstrated that BbLcLRR was tyrosine phosphorylated upon TCR stimulation, which was inhibited by Lck knockdown and was rescued by overexpression of BbLck. By mutating single tyrosine to phenylalanine (Y-F), we identified three tyrosine residues (Y539, Y655, and Y690) (3Y) of BbLcLRR as the major Lck phosphorylation sites. Reporter gene assays showed that overexpression of BbLcLRR but not the BbLcLRR-3YF mutant inhibited TCR-induced NF-κB activation. In Lck-knockdown T cells, the decline of TCR-induced IL-2 production was reversed by overexpression of BbLck, and this reversion was inhibited by co-expression of BbLcLRR but not the BbLcLRR-3YF mutant. Sequence analysis showed that the three tyrosine-containing sequences were conserved with the tyrosine-based inhibition motifs (ITIMs)motifs or ITIM-like motifs. Moreover, TCR stimulation induced the association of BbLcLRR with tyrosine phosphatases SHP1/2 and SHIIP1. Thus, we identified a novel immunoreceptor BbLcLRR, which is phosphorylated by Lck and then exerts a phosphorylation-dependent inhibitory role in TCR-mediated T-cell activation, implying a mechanism for the maintenance of self-tolerance and homeostasis of amphioxus immune system and the evolutionary conservatism of Lck-regulated inhibitory receptor pathway.